2015
DOI: 10.1590/1679-395110386
|View full text |Cite
|
Sign up to set email alerts
|

The Spiritually-Based Organization: A Theoretical Review and its Potential Role in the Third Millennium

Abstract: This paper examines whether the spiritually-based organization (SBO) can be regarded as an imperative for the third millennium. As a result, it draws on the literature review of organizational spirituality, psychology of religion, positive psychology, and spirituality leadership theory in order to support its conclusions, as well as it offers some research propositions. Overall, the evidence gathered throughout this paper suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 65 publications
0
37
0
10
Order By: Relevance
“…This literature review found evidence that POS concept has some theoretical convergence with other disciplines, particularly workplace spirituality, POB and positive psychology (VASCONCELOS, 2008(VASCONCELOS, , 2015see also LAVINE et al, 2014, for a broad analysis of the possibilities between POS and management spirituality and religion). All these disciplines provide a positive approach in management studies, yet each of them explores some particularities of it.…”
Section: Conclusion and Future Studiesmentioning
confidence: 92%
“…This literature review found evidence that POS concept has some theoretical convergence with other disciplines, particularly workplace spirituality, POB and positive psychology (VASCONCELOS, 2008(VASCONCELOS, , 2015see also LAVINE et al, 2014, for a broad analysis of the possibilities between POS and management spirituality and religion). All these disciplines provide a positive approach in management studies, yet each of them explores some particularities of it.…”
Section: Conclusion and Future Studiesmentioning
confidence: 92%
“…Pode-se dizer que as organizações estão começando a entender que elas não existem em um vácuo, mas sim em sociedade e que desempenham um papel importante neste mundo, além de que tudo que fazem impacta na vida de seus colaboradores. Sob a lente do paradigma da espiritualidade, as organizações são vistas como os mais responsáveis, conscientes e equitativos (VASCONCELOS, 2015).…”
Section: A Espiritualidade No Contexto Organizacionalunclassified
“…Isso corrobora com o que Vasconcelos (2015) defende sobre organização baseada na espiritualidade: a mesma tende a alcançar resultados adequados e a ser admirada pela sociedade como um todo. Diante disso, pode-se deduzir que esta organização amplia seu papel social, reconhecendo os princípios morais como um norteador e, simultaneamente, trabalhando eticamente para atender às necessidades da sociedade.…”
Section: A Espiritualidade No Contexto Organizacionalunclassified
See 2 more Smart Citations